PENERAPAN ASAS IN ABSENTIA TERHADAP KASUS KORUPSI - Abednego, Steven; Mompang L. Panggabean; Jimmy Simanjuntak (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2022)
The identified legal issue in this case is that, despite various efforts, the defendant could not be located within the jurisdiction of the Republic of Indonesia. A notable clause appears in the excerpt of the decision: "If the replacement money is not paid, the defendant's assets shall be seized and auctioned by the Prosecutor to cover the said amount. If the defendant does not have sufficient assets, a subsidiary imprisonment of two (2) years shall be imposed." This clause is particularly significant in the context of the application of the in absentia principle. Pursuant to Article 38 paragraphs (1) and (3) of Law Number 31 of 1999, in the event that a defendant has been lawfully summoned but fails to appear in court without valid justification, the case may be examined and adjudicated in their absence. Furthermore, the elucidation of Article 38(1) of Law No. 31/1999 highlights the phenomenon of the defendant's absence in trial proceedings due to having fled. The application of in absentia proceedings is faced with the fundamental principle that the presence of the defendant in a criminal trial serves to ensure legal certainty regarding the possibility of recovering state losses.